PENCIPTAAN BUKU REFERENSI MASJID TUA PADA ABAD XV DI SURABAYA SEBAGAI UPAYA PELESTARIAN CAGAR BUDAYA - Septiawan, Duanda Lis; Bahruddin, Muh; Sutikno, Sutikno (Jurnal Art Nouveau, 2015)
Abstract: Seeing the development of modern times currently still many old buildings in Surabaya one of which is building the mosque. The problem, of the old buildings not much known by the society. This is because not many media who publishes, especially through a book. In fact an old building is culture of the nation heritage that must be preserved so that known by next generations. See the background of the city of Surabaya known as a historic city of Surabaya of course have many cultural heritage , one of them is the mosque. The mosque is the place of worship for muslims and not a few also building mosque in surabaya who are categorized as old mosque. With age who are too old is certainly old mosque existing in surabaya having value of history and the philosophy behind the founding of the building and it cannot be forgotten offhand particularly by residents of the city of Surabaya own. In these research indicated that there are 3 mosque, mosque namely Rahmat Kembang Kuning mosque, Jamiâ Peneleh mosque, and Agung Sunan Ampel mosque which is considered old mosque built in the XV century in Surabaya. Â Keywords: Old Mosque, Cultural Heritage, Reference Book, Design, Preservation.